Ascorbic acid supplementation improves skeletal muscle growth in pacu (Piaractus mesopotamicus) juveniles: In vivo and in vitro studies - Zanella, Bruna Tereza Thomazini [UNESP]; Magiore, Isabele Cristina [UNESP]; Duran, Bruno Oliveira Silva; Pereira, Guilherme Gutierrez [UNESP]; Vicente, Igor Simões Tiagua [UNESP]; Carvalho, Pedro Luiz Pucci Figueiredo [UNESP]; Salomão, Rondinelle Artur Simões; Mareco, Edson Assunção; Carvalho, Robson Francisco [UNESP]; de Paula, Tassiana Gutierrez [UNESP]; Barros, Margarida Maria [UNESP]; Dal-Pai-silva, Maeli [UNESP] (MDPI, 2021)
In fish, fasting leads to loss of muscle mass. This condition triggers oxidative stress, and therefore, antioxidants can be an alternative to muscle recovery. We investigated the effects of antioxidant ascorbic acid (AA) on the morphology, antioxidant enzyme activity, and gene expression in the skeletal muscle of pacu (Piaractus mesopotamicus) following fasting, using in vitro and in vivo strategies. Isolated muscle cells of the pacu were subjected to 72 h of nutrient restriction, followed by 24 h of incubation with nutrients or nutrients and AA (200 µM). Fish were fasted for 15 days, followed by 6 h and 15 and 30 days of refeeding with 100, 200, and 400 mg/kg of AA supplementation. AA addition increased cell diameter and the expression of anabolic and cell proliferation genes in vitro. In vivo, 400 mg/kg of AA increased anabolic and proliferative genes expression at 6 h of refeeding, the fiber diameter and the expression of genes related to cell proliferation at 15 days, and the expression of catabolic and oxidative metabolism genes at 30 days. Catalase activity remained low in the higher supplementation group. In conclusion, AA directly affected the isolated muscle cells, and the higher AA supplementation positively influenced muscle growth after fasting.
Keywords: Anabolism; Ascorbic acid; Fasting; Myogenesis; Skeletal muscle growth